Division promotes adult stem cells to perform active niche competition. - Zhang, Q.; Zhang, Y.; Zhang, Q.; Li, L.; Zhao, S. (Genetics, 2023)
Adult stem cells maintain homeostatic self-renewal through the strategy of either population or single-cell asymmetry, and the former type of stem cells are thought to take passive while the latter ones take active competition for niche occupancy. Although the division ability of stem cells is known to be crucial for their passive competition, whether it is also crucial for active competition is still elusive. Drosophila female germline stem cells are thought to take active competition, and bam mutant germ cells are more competitive than wild-type germline stem cells for niche occupancy. Here we report that either cycB, cycE, cdk2, or rheb null mutation drastically attenuates the division ability and niche occupancy capacity of bam mutant germ cells. Conversely, accelerating their cell cycle by mutating hpo has an enhanced effect. Last but not least, we also determine that E-cadherin, which was proposed to be crucial previously, just plays a mild role in bam mutant germline niche occupancy. Together with previous studies, we propose that division ability plays a unified crucial role in either active or passive competition among stem cells for niche occupancy.